1-(4-Fluorobenzyl)-2-(pyridin-2-yl)-1H-benzimidazole - Çelik, Ömer (International Union of Crystallography, 2014)
In the title compound, C(19)H(14)FN(3), the dihedral angles between the benzimidazole unit (r.m.s. deviation= 0.017 Å) and the pyridine and benzene rings are 24.46 (4) and 81.87 (3)°, respectively. In the crystal, molecules are stacked along the a-axis direction by C—H⋯π interactions.